Changing It Up: Exploring the Lived Experiences of Alternative School Teachers Who Implement Restorative Practices - Long, Cindy (My University, 2026)
This qualitative case study explored how teachers at RISE Academy, an alternative school in the southeastern United States, experienced the shift from punitive discipline to restorative practices (RP). Using interviews, surveys, observations, and researcher fieldnotes, I examined how teachers understood RP, how they used it in daily practice, and what challenges they faced. Findings showed that teachers relied most on everyday restorative conversations—accountability talk, redirection, calm tone-setting, empathy, and consistent follow-up—which proved more practical than formal restorative circles. Safe, welcoming classrooms and a collective responsibility approach involving interventionists, crisis team members, and teachers helped prevent escalation and support students quickly.Teacher readiness varied. Four archetypes emerged—Specialists, Skeptics, Inherent Restorers, and Mindset Shifters—and survey data showed no significant correlations between overall self-efficacy and comfort with RP, though disciplinary self-efficacy approached significance. Challenges included limited time, emotional demands, uneven expectations, and the early removal of punitive options. Still, teachers supported the intent of RP and described meaningful student growth. Implications indicate that sustainable RP implementation requires steady administrative support, transparent communication, strong support personnel, structured tier documentation, differentiated professional learning, and modeling or peer testimony to build buy-in. Future research could develop an RP playbook and explore additional archetypes or ideologies to guide differentiated training.
Keywords: Education--Philosophy; Alternative schools; Teaching; Teachers; Dissertations, Academic; Restorative justice in schools; School discipline--Social aspects